2021
DOI: 10.1021/acs.est.1c01354
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Dynamic Technique DGT to Determine the Labile Pool Size and Kinetic Resupply of Pesticides in Soils and Sediments

Abstract: The diffusive gradients in thin films (DGT) technique has been successfully and widely applied to investigate the labile fractions of inorganic contaminants in soils and sediments, but there have been almost no applications to organic contaminants. Here we developed and tested the approach for the pesticide Atrazine (ATR) in a controlled soil experiment and in situ in an intact lake sediment core. The soil study explored the relationships between soil solution, DGT measured labile ATR and solvent extractable A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…They also found that the labile pool size, resupply capability, and kinetics of resupply are closely linked to redox conditions in the sediment and the reduction of Fe/Mn oxyhydroxides. However, our R profiles of inorganic pollutants showed more diverse patterns in the three sampling sites than those of Atrazine (Li et al, 2021). This result is not surprising, since the R value of an organic pollutant is depending on the resupply of the solid sediment phase, whilst that of inorganic pollutants is also influenced by the species distribution in the porewater.…”
Section: Vertical Profiles Of R Value For Trace Metals and Oxyanions ...mentioning
confidence: 57%
See 1 more Smart Citation
“…They also found that the labile pool size, resupply capability, and kinetics of resupply are closely linked to redox conditions in the sediment and the reduction of Fe/Mn oxyhydroxides. However, our R profiles of inorganic pollutants showed more diverse patterns in the three sampling sites than those of Atrazine (Li et al, 2021). This result is not surprising, since the R value of an organic pollutant is depending on the resupply of the solid sediment phase, whilst that of inorganic pollutants is also influenced by the species distribution in the porewater.…”
Section: Vertical Profiles Of R Value For Trace Metals and Oxyanions ...mentioning
confidence: 57%
“…Very recently, R value profiles in sediment porewater for Atrazine, an organic pollutant, were published (Li et al, 2021), and the authors concluded that the superficial layer of the sediment (0 to −2 cm of depth) had a greater capability to resupply Atrazine than the deeper layers. They also found that the labile pool size, resupply capability, and kinetics of resupply are closely linked to redox conditions in the sediment and the reduction of Fe/Mn oxyhydroxides.…”
Section: Vertical Profiles Of R Value For Trace Metals and Oxyanions ...mentioning
confidence: 99%
“…DGT technology has been widely developed to quantitatively monitor more than 180 different organic chemicals (including PFAS) in waters , as well as being used to study the speciation and bioavailability of inorganic chemicals in soils and sediments. , There are also a few pioneering studies on understanding the bioavailability of organics (pesticides, illicit drugs, and antibiotics) with DGT and plants/fish. Further systematic studies can help us better understand the bioavailability of organic chemicals in soils/sediments and their interactions with biota.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…As seen in Figure 2, at an early stage, t c mainly affects the change of R, resulting in a steep decline, consistent with previous studies for antibiotics, bisphenols, and pesticides. 29,33,53,54 The t c values ranged from 3.4 min (PFOS in soil B) to 529 min (PFBA in soil C) (Table 1). Smaller t c means that the response to the DGT uptake is fast; in general, smaller t c values were obtained for the PFSAs compared to the PFCAs (except PFBS in soil D, which is not readily explained), which implies that PFSAs in the soil solution were resupplied quickly by the solid phase compared to corresponding PFCAs with a similar chain length.…”
Section: Lability and Release Kinetics Of Pfas In Soilsmentioning
confidence: 99%
“…The availability of P is influenced by both its diffusion in soil solution and its release from soil solid. These dynamic processes can be analyzed by a model of DGTinduced fluxes in sediments and soils (DIFS) (Harper et al 1998), which has been used to accurately delineate the diffusion kinetics and resupply of metals and organic in soils and sediments (Guan et al 2017;Li et al 2021b;Pan et al 2021;Xu et al 2018). Additionally, Menezes-Blackburn et al (2016) combined DGT and DIFS model and found that desorption rates and resupply of P form solid were significantly correlated with FeO-P, Olsen-P, and NaOH-EDTA-P.…”
Section: Introductionmentioning
confidence: 99%